2014
DOI: 10.1242/jeb.103283
|View full text |Cite
|
Sign up to set email alerts
|

Moving without a purpose: an experimental study of swarm guidance in the Western honey bee (Apis mellifera Linnaeus)

Abstract: During reproductive swarming, honey bee scouts perform two very important functions. Firstly, they find new nesting locations and return to the swarm cluster to communicate their discoveries. Secondly, once the swarm is ready to depart, informed scout bees act as guides, leading the swarm to its final destination. We have previously hypothesised that the two processes, selecting a new nest site and swarm guidance, are tightly linked in honey bees. When swarms can be laissez faire about where they nest, reachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This ensures that a minimum number of individuals (the actual quorum number) are ready to move off [4]. Past research in meerkats, Suricata suricatta, for example, has found that a quorum of at least two and usually three meerkats emitting 'moving calls' are necessary for the whole group to move to a new foraging patch, and 'piping signals' in honeybees, Apis mellifera [6], and 'trills' in white faced capuchin monkeys, Cebus capucinus, [7] are required for collective departures to occur.…”
Section: Introductionmentioning
confidence: 99%
“…This ensures that a minimum number of individuals (the actual quorum number) are ready to move off [4]. Past research in meerkats, Suricata suricatta, for example, has found that a quorum of at least two and usually three meerkats emitting 'moving calls' are necessary for the whole group to move to a new foraging patch, and 'piping signals' in honeybees, Apis mellifera [6], and 'trills' in white faced capuchin monkeys, Cebus capucinus, [7] are required for collective departures to occur.…”
Section: Introductionmentioning
confidence: 99%
“…If, on the other hand, only bees that have experienced the quorum act as swarm guides, then none of the swarms in their experiments would have been able to fly. Makinson & Beekman [35] concluded that only bees that have directly experienced the quorum at the nest site guide the swarm, thereby ensuring that different groups of bees (those that have visited different potential nest sites) do not guide the flying swarm in different directions. We then need to assume that in the particular swarm Lindauer studied (see above) two nest sites reached a quorum simultaneously.…”
Section: Linking Nest-site Selection To Swarm Guidancementioning
confidence: 99%
“…They also needed a means for precise guidance of the swarm in flight towards that site. Because a vectorial consensus is insufficient to achieve these goals [35], cavity-nesting bees need to reach a near-unanimous decision prior to the swarm taking to the air. And because consensus is so important to A. mellifera, this species has evolved a 'stop-signal', aimed at silencing bees dancing for the non-chosen site [33].…”
Section: How Ecological Conditions Have Shaped the Bees' Nest-site Selection Processmentioning
confidence: 99%
See 2 more Smart Citations